Distinctive Gene Expression Patterns Define Endodormancy to Ecodormancy Transition in Apricot and Peach - Yu, Jiali; Conrad, Anna O.; Decroocq, Véronique; Zhebentyayeva, Tetyana; Williams, Daniel E.; Bennett, Dennis; Roch, Guillaume; Audergon, Jean-Marc; Dardick, Christopher; Liu, Zongrang; Abbott, Albert G.; Staton, Margaret E. (Frontiers in Plant Science, 2020)
Dormancy is a physiological state that plants enter for winter hardiness. Environmental-induced dormancy onset and release in temperate perennials coordinate growth cessation and resumption, but how the entire process, especially chilling-dependent dormancy release and flowering, is regulated remains largely unclear. We utilized the transcriptome profiles of floral buds from fall to spring in apricot (Prunus armeniaca) genotypes with contrasting bloom dates and peach (Prunus persica) genotypes with contrasting chilling requirements (CR) to explore the genetic regulation of bud dormancy. We identified distinct gene expression programming patterns in endodormancy and ecodormancy that reproducibly occur between different genotypes and species. During the transition from endo- to eco-dormancy, 1,367 and 2,102 genes changed in expression in apricot and peach, respectively. Over 600 differentially expressed genes were shared in peach and apricot, including three DORMANCY ASSOCIATED MADS-box (DAM) genes (DAM4, DAM5 and DAM6). Of the shared genes, 99 are located within peach CR quantitative trait loci, suggesting these genes as candidates for dormancy regulation. Co-expression and functional analyses revealed that distinctive metabolic processes distinguish dormancy stages, with genes expressed during endodormancy involved in chromatin remodeling and reproduction, while the genes induced at ecodormancy were mainly related to pollen development and cell wall biosynthesis. Gene expression analyses between two Prunus species highlighted the conserved transcriptional control of physiological activities in endodormancy and ecodormancy and revealed genes that may be involved in the transition between the two stages.